PENGETAHUAN PETANI DALAM MEMBUDIDAYAKAN TANAMAN JAGUNG HIBRIDA DI DESA WAKONTU KECAMATAN WADAGA KABUPATEN MUNA BARAT - Srofela Srofela; Dasmin Sidu; Sukmawati Abdullah (Universitas Halu Oleo, 2023)
Corn is one of the most important crops in the world along with wheat and rice. People living in many areas of Indonesia also use corn as a solid food as well as a source of carbohydrates, and this genetically engineered corn is now grown as a pharmaceutical product. Farmers' knowledge is everything that farmers know about crop business and business opportunities or job opportunities for farmers. This study aims to: Find out how the level of knowledge of farmers in cultivating hybrid corn plants in Wakontu Village, Wadaga District, West Muna Regency. This research was conducted in Wakontu Village, Wadaga District, West Muna Regency which was carried out from May to June 2022 with a total of 21 farmer respondents who were determined using the Slovin formula. Data analysis in this study used quantitative methods. The results showed that the level of knowledge of farmers in cultivating hybrid corn was in the medium category. where there are still some deficiencies in hybrid corn farming. This can be seen from the process of planting, maintenance to pest control.